Interpretacja pokutna Janowego opisu obmycia stóp uczniom przez Jezusa. Cz. 2: Argument odwołujący się do antropologii kulturowej - Kubiś, Adam (The Biblical Annals, 2018)
The article argues – within the sacramental framework – for a specifically penitential interpretation of the Johannine foot-washing narrative, adding a new argument in favor of a penitential reading of the pericope. Prefaced by a list of eleven arguments in favor of this approach, a new rationale is then presented, this time based on advances in cultural anthropology as reflected in the works of J.H. Neyrey and R. DeMaris. Neyrey’s reading of Jn 13:1-20 sees both a rite of status transformation (in vv. 6-11) and a ceremony confirming roles and statuses (in vv. 12-20); this is further enriched by DeMaris’s reading arguing for the presence of one particularly Johannine rite, which confirmed and renewed the disciples’ status gained through baptism. Both of the above readings are now reinterpreted by means of a sacramental key. As a result, the meaning of the foot-washing points toward a sacramental practice, namely a penitential rite of confession and remission of post-baptismal sins, as reflected in other Johannine texts (Jn 20,22-23; 1 Jn 5,14-16).